(untitled) (International Journal of Engineering and Computer Science, 2015)
This paper deals with the implementation of a system which is capable of tracking and scheduling of State Transport Bus.For this implementation we are using Radio Frequency Identification(RFID).Proposed system can save the efforts of depot staff to maintain the schedules also it can save paper ,in other words it is eco-friendly .The proposed system can inform depot managers and other staff members whether the bus is arriving on time ,early or late .Passengers can also checkout last bus depot visited by the respective bus.